Discrete event simulation demonstrator for G54SIM - Ahmed, Nzar Rashid (2014)
Recent computer multimedia system developments have promoted computer capability to support learning process. This is through supporting novelty and interactivity, which are two significant concepts of learning and make multimedia systems more effective than classic classrooms. There are various computer programs which are used for multimedia learning in different aspects. However, those programs which support discrete event simulation, does not provide comprehensive information about three-phase approach, which is an approach of this simulation. Therefore, a program to support learning three-phase approach has been developed within this project, regarding learning perspectives. To develop this program, object oriented methods have been used to make the program easy to extend. Also, object oriented design pattern has been used to keep the system open to extend and close to modifications. To determine to what extent the program reaches the goal, user testing has been performed through recruiting students from different disciplines. It has concluded that the program can support learning this particular simulation to a good extent, through the provided features such as graphical representations, animations, and interactions.